1995
DOI: 10.1152/ajpcell.1995.269.2.c312
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin stimulates myometrial calcium-activated potassium channel activity via protein kinase A

Abstract: Relaxin, a hormone that is elevated during pregnancy, can suppress myometrial contractile activity. Ca(2+)-activated K+ channels (KCa) play a role in the modulation of uterine contractions and myometrial Ca2+ homeostasis and have been implicated in the control of smooth muscle excitability. We now show that relaxin stimulates KCa channels in cell-attached patches in a cell line derived from term pregnant human myometrium. This effect was prevented by the protein kinase A (PKA) antagonist, the Rp diastereomer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 0 publications
2
54
1
Order By: Relevance
“…Relaxin binding to its cognate receptor(s) and postreceptor signalling are likely to be complex and cell-and tissue-specific. Relaxin has been reported to enhance cAMP formation in human endometrial (29) and anterior pituitary cells (30), to inhibit Ca 2 ϩ influx in myometrial cells (31) and mast cells (32), and to induce protein kinase C translocation from cytosol to membranes in endometrial cells (33). Additionally, binding of relaxin to certain cell types is estrogen-dependent while binding to others is not (34), and certain phenotypic alterations are dependent on the presence of both relaxin and estrogen while others are not (17).…”
Section: Discussionmentioning
confidence: 99%
“…Relaxin binding to its cognate receptor(s) and postreceptor signalling are likely to be complex and cell-and tissue-specific. Relaxin has been reported to enhance cAMP formation in human endometrial (29) and anterior pituitary cells (30), to inhibit Ca 2 ϩ influx in myometrial cells (31) and mast cells (32), and to induce protein kinase C translocation from cytosol to membranes in endometrial cells (33). Additionally, binding of relaxin to certain cell types is estrogen-dependent while binding to others is not (34), and certain phenotypic alterations are dependent on the presence of both relaxin and estrogen while others are not (17).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms involving, inter alia, endothelin, NO and relaxin (Goldsmith et al 1995, Dong & Yallampalli 1996 may also regulate myometrial contractility. In the rat, a decline in luteal relaxin production will contribute to increased excitability, removing relaxin's inhibitory actions, mediated by protein kinase A, on myometrial cells (Meera et al 1995); this may involve interference with G q/11 which mediates oxytocin actions . Thus, while oxytocin may play some role in the initiation of labour, there are certainly other uterine mechanisms that can substitute for it in its absence, and which indeed may play a more dominant role.…”
Section: Initiation Of Deliverymentioning
confidence: 99%
“…The molecular mechanism by which channel modulation occurs is unclear, however, since studies have indicated that single maxi-K channels are regulated by phosphorylation and by phosphorylation-independent G protein interactions (5,6,(11)(12)(13)(14). Further, with respect to channel phosphorylation, maxi-K channel stimulation has been attributed to channel phosphorylation by cAMP-dependent protein kinase (5,6,11,15,16), by cGMP-dependent protein kinase (17)(18)(19)(20)(21), and by channel dephosphorylation (19,22,23). Maxi-K channels are composed of at least two dissimilar subunits: the ␣ subunit, which forms the channel pore (24 -27), and the ␤ subunit (28 -30), which modifies the voltage and calcium sensitivity of the pore-forming subunit (31).…”
mentioning
confidence: 99%